Analisa dan Perancangan Sistem Informasi Inventory Barang dengan Metode RAD (Rapid Application Development) pada CV. Agung Rejeki - Agus Priyanto (UNIVERSITAS PELITA HARAPAN, 2022)
CV. Agung Rejeki is a company engaged in the provision of building equipment. Currently, recording inventory reports at CV. Agung Rejeki is not yet optimal, causing the company's performance to be hampered. The purpose of the results of this study is to create a basic framework for a computer-based Inventory Information System to help business processes at CV. Agung Rejeki and provides information in the form of views and reports that are appropriate and integrated in each unit in the CV. Great Fortune. RAD is a method of developing information systems with a relatively short time. In normal information system development, it takes a minimum of 180 days, but using the RAD method, the system can be built in 30-90 days. By applying the RAD (Rapid Application Development) model to a computerized inventory system that is also equipped with a visual basic programming language and a crystal report, it can help in making quick decisions. Data modeling architecture that defines 7 tables, defines 3 entities involved in the inventory process of goods in CV. Agung Rejeki, namely Administrators, Employees, Sales. Furthermore, the use of the RAD (Rapid Application Development) model to realize an inventory information system can provide optimal results. The system has got its interests, the inventory data manager and responds to the needs of consumers to obtain information.